Features of the use of innovative technologies in the personnel management system - Іryna Dashko; Liubomyr Mykhailichenko (Економічний форум)
Researched and analyzed modern personnel management technologies. The basic principles of the innovative economy have been studied. It was determined that in the conditions of technological development, the approach to personnel management has fundamentally changed, and standard methods are already outdated and ineffective. The main technological methods of management in the conditions of technology development are analyzed. It is noted that a significant role is played today by the system of training employees using innovative technologies, which is one of the most optimal areas of investment activity of a modern organization. It was determined that the system of modular education and personnel development is gaining particular popularity, which involves the development of a program for the development of individual categories of personnel based on a set of thematic, interconnected blocks or so-called modules. The main areas of application of innovative technologies in the personnel management system are substantiated. It is noted that today it is extremely necessary not only to ensure the proper level of personnel management, but also to create an effective motivation system, which is mainly based on the application of a system of various bonuses and bonuses that stimulate the employee to work more efficiently to achieve a certain result. It has been studied that the most important indicator of motivation is the salary level, which depends on the employee's desire to work in the organization. A comprehensive analysis of the application of the KRI system for evaluating the effectiveness of activities was carried out on the example of a sales manager. It has been studied that with the help of the employee's performance evaluation system, it is possible to evaluate the result of his work. A KPI matrix is ​​proposed for more effective motivation, using the example of sales managers. The introduction of bonuses is proposed, which should have a directly proportional effect on the increase of both the salary of sales managers and the profit of the organization as a whole. It is noted that the implementation of the KRI system at the enterprise will allow the management to see the real picture of the employment of its employees and introduce a bonus for the sales manager based on the effectiveness of the work performed